Impact evaluation of Funda Wande in-service teacher coaching intervention: Findings from the first year - Meiring, Christiaan (School of Economics, 2021)
Acknowledging the limited opportunities for South African teachers to acquire specialized knowledge in teaching reading, particularly in African Languages, the Non-Governmental Organisation Funda Wande is providing an integrated package of support to train Foundation Phase literacy teachers in how to teach reading for meaning in African languages. The pilot intervention evaluated here takes place in three urban schooling districts in South Africa's Eastern Cape province. The intervention is implemented in partnership with the Eastern Cape Department of Education (ECDoE). The Funda Wande in-service training model builds on international best practice and lessons learnt from domestic iterations of integrated teacher training and support models, prominently amongst which are the Department of Basic Education (DBE)-led Early Grade Reading (EGRS) studies Funda Wande provides a bouquet of home language print resources to learners and classrooms. Teachers also receive an integrated package of curriculum aligned lesson plans, assessment booklets and online pedagogic resources. In-classroom teacher coaching provides support, monitoring and feedback for teachers on how to implement new teaching techniques and make use of materials. The Funda Wande course trains teachers and their Heads of Department (HODs) on how to teach reading for meaning in African languages. The course content provides teachers with knowledge on the morphology of African languages and how learners learn to read in them, whilst supporting materials and in-person coaching equips teachers to implement the instructional techniques in practice. The primary aim of the evaluation is to assess whether the Funda Wande intervention is effective in changing teacher's instructional behaviour and improving early reading outcomes. More specifically, the programme's is evaluated with reference to its self-stated goal: that all learners should be able to read for meaning in their home language by the end of Grade 3. The specific reading outcomes assessed are grade relevant foundational reading and reading comprehension skills. A randomized control trial (RCT) is used to estimate the causal impact of the programme on early literacy outcomes with schools randomized into one of two arms – Funda Wande and control – in three urban and peri-urban education districts. All schools in the evaluation are no fee public schools with an isiXhosa language of learning and teaching. After one year of programme exposure, the intervention impact on the treated group of Grade 1 and 2 learners' reading proficiency is 0.17 standard deviations. Translated into the amount of learning that took place in comparison schools, or ‘business as usual' learning environments, this effect equals between 20 to 27 percent of a year's worth of learning for Grade 2 learners and 33 to 58 percent of a year's learning for Grade 1 learners. Dependent on the outcome measure used, the programme impacts therefore range roughly between one and two terms of learning in comparison status quo classrooms. The programme effects are positive across all the sub-domains of reading proficiency that could be measured reliably. For Grade 1 learners, intervention impacts were the largest on foundational decoding skills - correctly identifying letter sounds and being able to manipulate phonemes. At this early stage of Grade 1 leaners' development trajectories, these are the skills that are required to decode words, read more fluently and eventually progress to reading for meaning. The impacts on downstream higher order reading comprehension skills are only detectable for Grade 2 learners. Consistent with other results from the recent literature, these findings support the idea that learners require a range of foundational literacy abilities before they can read with some level of fluency. In turn, learners need to read with a certain minimum level of speed and accuracy in order to comprehend what they are reading. A particularly encouraging finding from a policy perspective is that the intervention has fairly consistent positive impacts for learners across the distribution of baseline reading proficiency. Programme impacts also do not vary with of learners' relative rank for reading proficiency within their classrooms. Previous research suggests that improving reading outcomes for learners with the lowest levels of foundational reading skills in an absolute sense is particularly challenging. A related finding is suggestive evidence that the programme helps boys in treatment schools catch up with their generally more proficient girl counterparts, but only in Grade 2 and with the extent of catch-up contingent on the boys' baseline levels of reading proficiency. At this stage only suggestive results are presented for the potential mechanisms at play. Evidence across more than one indicator suggests that teachers in intervention schools are more likely to a) be more attuned to the actual reading proficiency levels of the learners in their class (both in terms of whether learners are at the top or the bottom of the distribution and how the class performs overall); b) to make use of graded readers - which were provided equivalently to both treatment and control schools - more frequently; and (c) to use instructional techniques that have previously shown to facilitate more individualised forms of learner reading practice and -teacher feedback. Future rounds of assessments and in-depth qualitative classroom observations will delve deeper into both the potential mechanisms at play, as well as the potential characteristics of the Funda Wande intervention that result in it being effective in shifting learning outcomes for leaners across the distribution of reading proficiency levels (and for learners with the lowest levels of reading proficiency in particular). Other unanswered question at this stage relate to the details that would allow one to compare the absolute- and cost-effectiveness of the programme to similar interventions in the literature. The results here add to the growing body of evidence that makes a strong case for the crucial complementary role of high-quality teacher coaching and continuous follow-up support in programmes that focus on shifting teachers' instructional practice. Consistent with the results from similar interventions in Kenya, Uganda and South Africa, the Funda Wande intervention improves learning outcomes through combining material provision, a structured sequence of lessons, alignment around some central curriculum, and supporting teachers in “learning by doing” through teacher professional development support.